Spatio-temporal patterns of pancreatic cancer cells expressing CD44 isoforms on supported membranes displaying hyaluronic acid oligomers arrays - Kaindl, Thomas; Rieger, Harden; Kaschel, Lisa-Mareike; Engel, Ulrike; Sleeman, Jonathan P.; Tanaka, Motomu (PLOS ONE, 2012)
In this paper, we designed a quantitative model of biological membranes by the deposition of planar lipid membranes on solid substrates (called supported membranes), and immobilized biotinylated oligomers of hyaluronic acid (oligo-HA, 6-8 disaccharide units in length) to the membrane surface via neutravidin cross-linkers. By controlling the self-assembly of biotinylated lipid anchors, the mean distance between the oligo-HA molecules on the membrane could be controlled to nm accuracy. The adhesion and motility of pancreatic adenocarcinoma cells expressing different splice variants of the HA-binding cell surface receptor CD44 on these surfaces were investigated quantitatively. The combination of label-free, time-lapse imaging of living cells and statistical analysis suggests that the static morphology (global shape and cytoskeleton remodeling) of cells, their stochastic morphological dynamics, and the probability of directed motion reflect the metastatic behaviour of the cancer cells.
Gesehen am 19.05.2017